CARACTERIZAÇÃO DO LEITE E QUEIJO ARTESANAL PRODUZIDO NA REGIÃO FRONTEIRA NOROESTE DO ESTADO DO RS - Fiorentini, Angela M.; Hermanns, Gislaine; Funck, Graciele D.; Schmidt, Jéssica T.; Richards, Neila S.; Vicenzi, Raul (Salão do Conhecimento, 2013)
Resumo